Strengthening PAI Learning to Improve Islamic Values at Sungai Mulia 5 Gombak Guidance Studio Kuala Lumpur Malaysia - Rofiah, Khusnur (Sultan Journal of Social Sciences and Humanities, 2025)
The purpose of this community service program is to strengthen Islamic Religious Education (PAI) learning to improve the understanding, practice, and internalization of Islamic values among students at the Sungai Mulia 5 Guidance Center in Gombak, Kuala Lumpur, Malaysia. This community service method utilizes the Asset-Based Community Development (ABCD) approach, which focuses on exploring, utilizing, and developing community assets through the stages of Discovery, Dream, Design, and Destiny. The success of the PAI strengthening program at the Sungai Mulia 5 Guidance Center is supported by the active involvement of the center's management, teachers, volunteers, students, parents, and community leaders who play their roles according to their respective capacities. This participatory collaboration makes the center a community capable of developing meaningful and sustainable Islamic Religious Education (PAI) learning. The results of the community service program using the ABCD approach at the Sungai Mulia 5 Guidance Center demonstrate an increase in students' understanding, participation, and enthusiasm in PAI learning. Islamic extracurricular activities have successfully fostered a spirit of togetherness and strengthened the practice of Islamic values in daily life. Islamic character traits such as discipline, responsibility, and respect are increasingly evident in the students' behavior. Furthermore, the studio environment has become more religious, orderly, and conducive thanks to the full support of teachers, parents, and the surrounding community.